Leanness assessment in automotive industry: case study approach. (2018) - Galankashi, Masoud Rahiminezhad; Helmi, Syed Ahmad; Hisjam, Muhammad; Rahim, Abd Rahman Abdul
The main objective of this study is to develop a framework to assess the leanness of companies in the automotive industry. Although lean manufacturing (LM) has been discussed in previous studies, leanness assessment is less investigated. Therefore, to fill this gap, this study is conducted to assess the leanness of three manufacturing companies with regard to different supply chain drivers. Principally, six drivers of facility, inventory, transportation, sourcing, pricing and information are selected as the major components of supply chains. The lean-related activities of each driver are identified and a benchmarked questionnaire is applied to assess the leanness of companies. Next, different leanness of each driver is calculated accordingly. An overall quantity of leanness is also provided for each company. Finally, some managerial insights and future research directions are recommended. According to the results, second case study has the highest degree of leanness in comparison to other two companies. In addition, this company has the best performance with regard to each supply chain driver.